PHARMACOTHERAPY OF ARTERIAL HYPERTENSION IN ELDERLY PATIENTS: FOCUS ON OCTOGENARIANS - E. A. Ushkalova; O. N. Tkacheva; N. K. Runikhina; N. A. Chukhareva; A. Yu. Bevz (Рациональная фармакотерапия в кардиологии, 2016)
Pharmacotherapy of arterial hypertension in the elderly is discussed. Russian and international guidelines are presented with a focus on target levels of blood pressure and drugs of choice in these patients. Issues of efficacy and safety of antihypertensive therapy in patients aged 80 years and older are considered.